Nitrous oxide as a function of oxygen and archaeal gene abundance in the North Pacific - Mark Trimmer (Nature Portfolio, 2016)
Understanding the production processes behind oceanic sources of nitrous oxide (N2O), a potent greenhouse gas, is of critical importance. Here, the authors reveal an archaeal-mediated N2O production pathway in the North Pacific, which increases exponentially with decreasing oxygen.